Unravelling Encounters : Ethics, Knowledge, and Resistance under Neoliberalism - Janzen, Caitlin, 1982-; Smith, Kristin, 1965-; Jeffery, Donna, 1955- (Wilfrid Laurier University Press, 2015)
This multidisciplinary book brings together a series of critical engagements regarding the notion of ethical practice. As a whole, the book explores the question of how the current neo-liberal, socio-political moment and its relationship to the historical legacies of colonialism, white settlement, and racism inform and shape our practices, pedagogies, and understanding of encounters in diverse settings. The contributors draw largely on the work of Sara Ahmed's Strange Encounters: Embodied Others in Post-Coloniality, each chapter taking up a particular encounter and unravelling the elements that created that meeting in its specific time and space. Sites of encounters included in this volume range from the classroom to social work practice and from literary to media interactions, both within Canada and internationally. Paramount to the discussions is a consideration of how relations of power and legacies of oppression shape the self and others, and draw boundaries between bodies within an encounter. From a social justice perspective, Unravelling Encounters exposes the political conditions that configure our meetings with one another and inquires into what it means to care, to respond, and to imagine oneself as an ethical subject.